Other books received - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
FAO, 1986. The Dynamics of Rural Poverty. FAO, Rome, 232 panes Dixon, R. A. (ed.), 1985. Plant cell culture - a practical approach. IRL Press, PO Box 1, Eynsham, Oxford OXO 1JJ UK Jainudeen, M. R. et al., (eds.) 1987. Livestock production and...